(untitled) (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2017)
During the Augustan period, some 18 cities in Roman Italy constructed city walls around their urban centres – the last cluster of city walls to be built here until the late third century AD. There was no defensive imperative for walls at this time, as the heart of the empire was relatively peaceful, so what motivated urban communities to undertake such a time-consuming and expensive project? This article notes the superficial similarities in the physical form of Augustan city walls and their towers and gateways, but downplays the notion of a shared design model. Rather, it argues that a more important theme which links this group of city walls was their symbolic and ideological meaning. The common ways in which Augustan city walls engaged with their physical and cultural environment are examined, and shared characteristics such as the visual prominence and imposing display of city walls and gateways, connections with pre-Roman sanctuaries and foundation rituals, and imperial involvement and patronage are explored. The article concludes that in terms of typology, Augustan city walls are surprisingly diverse in their physical form despite apparent congruencies, but that they share important political and social themes. In summary, Augustan city walls were built to impress – icons of visual dominance and cultural manipulation of the landscape, promoting the status and prestige of the city they surrounded.